Images of the Russian threat as printed at the border - Oivo, Teemu (University of Lappland, 2023)
Since Finland’s declaration of independence from Russia in 1917, the actuality of threats emanating from images of Russia has been one of the most debated topics in Finnish academic, political, and open discussion forums alike. Reflecting on previ- ous studies, I have qualitatively examined how threats associated with such images were represented and challenged in 2016. My case study is based on an analysis of Karjalainen, the provincial newspaper of North Karelia, which borders another Barents Euro-Arctic Region, the Republic of Karelia, a subject of the Russian Federation. The daily media discussions on the pages of Karjalainen provide a view to the intersec- tion of regional, national, and international news. I compare the newspaper contents to threats associated with Russia as recognized in previous research literature. The threat images are represented contextually in different ways when they are related to history, contemporary international affairs, the Russian people, and border life, as well as the less visible topics of the economy and the environment. The newspaper content rehearses the dominant image of Russia as a geopolitical threat, but even those who wrote about this, often problematized simplified images of an entire country. Peer reviewed